Working Principles Of Constant Current Regulator (CCR) As Charge With Constant Flow At The Airport International Jendral Ahmad Yani Semarang - Fariza Haqi; Yuliarman Saragih; Rahmat Hidayat (Widya Teknik, 2021)
The Airfield Lightning System (ALS) is an important part of this airport operations. Without the help of these lights, landings and flight departures can be very dangerous. It can be said to be Airfield Lightning System (ALS) is the key in handling the safety of the operating authority aviation services. The Airfield Lightning System (ALS) really requires intensity fixed and unchanging light so that the pilot can see the lights that clearly. Given a very vital function in aviation services required a power supply that supports the operation of the Airfield Lightning System (ALS). The required power supply system must of course meet Airfield's criteria Lightning System (ALS). Because a constant current is needed, then di use the Constant Current Regulator (CCR). The supporting components are also involved designed so that Runaway Lightning operations can take place continuously maximum, and can support flight safety.